Políticas de infraestrutura de transportes no Brasil : investimentos, multimodalidade e configuração regional no plano nacional de logística e transporte (PNLT) - Medeiros, Paulo Vinícius Menezes de (2014)
The present work aims at analyzing the transport infrastructure in Brazil, with a focus on the Plano Nacional de Logística e Transporte (PNLT), highlighting investments, matrix and regional setting. For this, there was a brief historical survey of facing investment in transport infrastructure in the Brazil national policies. This Plan has significant importance because it marks the rescue of planning in the medium and long term the sector in the country\'s history. The previous and the nature of PNLT are presented and discussed as they were encompassed the main modal encompassed in the plan: the waterway, the pipeline, mainly, rail and road. This paper work up the qualitative and quantitative aspects of the evolution of these modes, using data from the Banco de Informações e Mapas de Transportes (BIT) and the Confederação Nacional de Transporte (CNT), among others, as well as joint investment on Programa de Aceleração do Crescimento (PAC) distributed by region, considering the division by state and regions. The study confirms the relevance of PNLT to resume planning of transport infrastructure in the country, identifying an increase in infrastructure investments and measures in favor of restoring the transport matrix in a favorable macroeconomic context. Nevertheless, there is no indication, in principle, of relevant changes in the regional setting, given the continuing concentration of investments in regions of higher economic dynamics.